MiR-129-5p: A key factor and therapeutic target in amyotrophic lateral sclerosis. (July 2020) - Loffreda, Alessia; Nizzardo, Monica; Arosio, Alessandro; Ruepp, Marc-David; Calogero, Raffaele A.; Volinia, Stefano; Galasso, Marco; Bendotti, Caterina; Ferrarese, Carlo; Lunetta, Christian; Rizzuti, Mafalda; Ronchi, Antonella E.; et al.
Highlights: miR-129-5p is increased in different models of SOD1-linked ALS and in peripheral blood cells of sporadic ALS patients. miR-129-5p upregulation causes the downregulation of one of its targets: the RNA-binding protein ELAVL4/HuD. ASO targeting miR-129-5p in SOD1(G93A) mice results in significant improve in survival and in neuromuscular phenotype. Overexpression of miR-129 inhibits neurite outgrowth in vitro, while its inhibition with antagomir rescues the phenotype in vivo . Abstract: Amyotrophic lateral sclerosis (ALS) is a relentless and fatal neurological disease characterized by the selective degeneration of motor neurons. No effective therapy is available for this disease. Several lines of evidence indicate that alteration of RNA metabolism, including microRNA (miRNA) processing, is a relevant pathogenetic factor and a possible therapeutic target for ALS. Here, we showed that the abundance of components in the miRNA processing machinery is altered in a SOD1-linked cellular model, suggesting consequent dysregulation of miRNA biogenesis. Indeed, high-throughput sequencing of the small RNA fraction showed that among the altered miRNAs, miR-129-5p was increased in different models of SOD1-linked ALS and in peripheral blood cells of sporadic ALS patients. We demonstrated that miR-129-5p upregulation causes the downregulation of one of its targets: the RNA-binding protein ELAVL4/HuD. ELAVL4/HuD is predominantly expressed in neurons, where it controls several key neuronal mRNAs. Overexpression of pre-miR-129-1 inhibited neurite outgrowth and differentiation via HuD silencing in vitro, while its inhibition with an antagomir rescued the phenotype. Remarkably, we showed that administration of an antisense oligonucleotide (ASO) inhibitor of miR-129-5p to an ALS animal model, SOD1 (G93A) mice, result in a significant increase in survival and improved the neuromuscular phenotype in treated mice. These results identify miR-129-5p as a therapeutic target that is amenable to ASO modulation for the treatment of ALS patients.